Microbial activity in soils from the Făgăraș Mountains - Carla Andreea CULDA; Rahela CARPA; Călin DEJEU; Anca Livia BUTIUC (Studia Universitatis Babeș-Bolyai. Biologia, 2019)
The aim of this paper was to assess the microbial activity and detection of some enzymes from soils of mountain zones in order to understand the complex processes that occur in these habitats. The sampling sites are located in three zones from the Făgăraș Mountains (woodside, forest and grassland). Six soil samples from these zones were subjected to microbiological and enzymological studies. The physical-chemical analyses were carried out using a portable multiparameter (pH, Eh, electrical conductivity and salinity). The following four ecophysiological bacterial groups have been studied: aerobic mesophilic heterotrophs, ammonifiers, nitrifiers and denitrifiers. The presence of all ecophysiological bacterial groups was registered in all the soil samples. The studied bacterial groups present fluctuations according with the sampling zones. The descending ranking of their abundance in the soil samples was: aerobic mesophilic heterotrophs, ammonifiers, nitrifiers, denitrifiers. Based on the bacteria number of each ecophysiological group, the bacterial indicators of soil quality (BISQ) were calculated. All of the four enzymatic activities analysed in soils (phosphatase, catalase, actual and potential dehydrogenase) were registered at every sampling site. Based on the absolute values of enzymatic activities, the enzymatic indicator of soil quality (EISQ) was obtained. The EISQ and BISQ values indicate a good intensity of these activities in all the analysed zones.